TERAPAN ETOS KAIZEN DALAM “MENINGKATKAN KELAS” BISNIS KULINER BERKEARIFAN LOKAL - Pranawukir, Iswahyu; Misnan, Misnan; Sukma, Agus Hitopa (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to provide counseling to the UMKM Association of Komunitas Sukses Berjamaah Indonesia (KSBI) in South Jakarta regarding the application of the Kaizen ethos in improving the quality and success of their culinary business based on local wisdom. This counseling aims to provide an understanding of the concept of Kaizen ethos and encourage KSBI members to apply it in their culinary business. In this activity, an interactive approach method was used through discussions and case studies to understand the potential for improving local wisdom-based culinary businesses. The participants were invited to identify problems, challenges, and opportunities in their culinary business, as well as to utilize local wisdom as an added value in the business. Key Kaizen principles, such as elimination of waste, quality improvement, employee engagement, and continuous improvement cycle, were explained and applied in the context of KSBI's culinary business. Through the delivery of implementation strategies and successful case examples, participants were given practical guidance to apply the Kaizen ethos in their culinary business. In addition, Q&A and discussion sessions provided an opportunity for KSBI members to share their experiences and obtain solutions to the questions and problems they faced. The results of this activity had a positive impact on the members of the UMKM Community Sukses Berjamaah Indonesia (KSBI) in South Jakarta, focusing on continuous improvement and utilization of local potential, the participants managed to improve their operational efficiency and the quality of their culinary products. Awareness of the importance of innovation and adaptation to market changes has also increased, thus opening up opportunities to expand markets and strengthen the competitiveness of local wisdom-based culinary businesses through the application of the Kaizen ethos.